Mapping Bitcoin Research in Information Systems: A Comprehensive Bibliometric Analysis (2008–2025) - Akhlis Munazilin; Mochamad Agung Wibowo; Rizky Parlika (ISB Atma Luhur, 2026)
Bitcoin has been a major focus of interdisciplinary research in information systems, finance, and economics since its emergence in 2008. Despite the extensive literature on Bitcoin, patterns of intellectual collaboration, the evolution of research themes, and research gaps have not been comprehensively mapped. This study presents a bibliometric analysis of 3,312 scientific articles indexed by Scopus from 2008 to May 2025, using a quantitative approach based on Bibliometrix. The analysis includes publication trends, author and institutional collaboration networks, co-citation mapping, and thematic clusters based on keywords. The results reveal five dominant themes: (1) blockchain development beyond crypto, (2) regulatory challenges and global adoption, (3) Bitcoin price volatility, (4) impacts on the global financial system, and (5) social implications in developing countries. The study also identifies an epistemological fragmentation between technical and policy approaches. These findings reinforce the need for an integrated multimodal approach that combines market data, sentiment analysis, and regulatory context to develop more robust predictive models. This study is the first comprehensive bibliometric review of Bitcoin in global scope that explicitly links findings to information systems research opportunities.